Prevalence of respiratory symptoms and lung function impairments among woodworkers in Gondar City - Eshetu Abera Worede; Mengesha Genet; Wudneh Simegn; Giziew Abere; Sefinew Tilahun; Mastewal endalew; Eyayaw Adisu Demeke; Garedew Tadege Engedaw; Hailemariam Feleke; Yifokire Tefera Zele; Jember Azanaw (Scientific Reports)
Abstract Respiratory symptoms and lung function impairments are concerns in the woodworking industry. In Ethiopia, the woodwork industry has been growing; however, there is limited data on pulmonary function, respiratory symptoms, and risk factors among woodworkers. This study aimed to assess the prevalence of impaired lung function and respiratory symptoms and determine their associated risk factors among woodworkers in Gondar City, Ethiopia. A comparative cross-sectional study was conducted, involving 185 woodworkers and 176 controls. Spirometry was used for Lung function tests. The data were collected using a questionnaire in Kobo Toolbox software. Statistical analyses, including ANOVA, t-test, and logistic regression were done in SPSS version 26. Almost all participants (96.4%) were male. The proportions of obstructive, restrictive, and mixed lung function impairments in woodworkers and control groups were 7.6% vs. 2.8%, 4.86% vs. 3.98%, and 1.08% vs.0%, respectively. The proportion of chronic respiratory symptoms in woodworkers and control groups was 35.5% vs. 12.7% with the proportion of cough (19.9% Vs 6.6%), phlegm (21.1% Vs 5.8%), wheezing (9.4% Vs 3.9%), shortness of breath (19.9Vs 6.6%), and breathlessness (13.3% Vs 8.3%). In woodworkers, and pooled models, the absence of a local exhaust ventilation system, working more than eight hours per day, being unable to use filter masks, and being unable to do physical exercise were significantly associated with respiratory symptoms. Forced Expiratory Volume in 1 s/Forced Vital Capacity ratio (FEV1/FVC ratio) (P = 0.001) and Mid-Expiratory Flow between 25% and 75% (MEF25%-75%) significantly decreased with work experience (P = 0.001). Woodworkers had higher rates of obstructive, restrictive, and mixed lung function impairments and more respiratory symptoms. Prioritizing workplace ventilation and the use of respiratory protective devices is crucial for mitigating these risks.